Frontiers in quantifying wildlife behavioural responses to chemical pollution. (1st March 2022) - Bertram, Michael G.; Martin, Jake M.; McCallum, Erin S.; Alton, Lesley A.; Brand, Jack A.; Brooks, Bryan W.; Cerveny, Daniel; Fick, Jerker; Ford, Alex T.; Hellström, Gustav; Michelangeli, Marcus; Nakagawa, Shinichi; et al.
ABSTRACT: Animal behaviour is remarkably sensitive to disruption by chemical pollution, with widespread implications for ecological and evolutionary processes in contaminated wildlife populations. However, conventional approaches applied to study the impacts of chemical pollutants on wildlife behaviour seldom address the complexity of natural environments in which contamination occurs. The aim of this review is to guide the rapidly developing field of behavioural ecotoxicology towards increased environmental realism, ecological complexity, and mechanistic understanding. We identify research areas in ecology that to date have been largely overlooked within behavioural ecotoxicology but which promise to yield valuable insights, including within‐ and among‐individual variation, social networks and collective behaviour, and multi‐stressor interactions. Further, we feature methodological and technological innovations that enable the collection of data on pollutant‐induced behavioural changes at an unprecedented resolution and scale in the laboratory and the field. In an era of rapid environmental change, there is an urgent need to advance our understanding of the real‐world impacts of chemical pollution on wildlife behaviour. This review therefore provides a roadmap of the major outstanding questions in behavioural ecotoxicology and highlights the need for increased cross‐talk with other disciplines in order to find the answers.